http://ocw.mit.edu/courses/electrical-engineering-and-computer-science/6-071j-introduction-to-electronics-signals-and-measurement-spring-2006/lecture-notes/nodal_mesh_methd.pdf

I'm curious about the setup of the equations of the first problem on page 17.

my equations are

6i_a+4(i_a-i_b)=12

2(i_b-i_c)+4(i_b-i_a)=6

2(i_c-i_b)+2i_c=2

which simplifies down to

10i_a-4i_b=12

-2i_a+6i_b-2i_c=6

-2i_b+4i_c=2

The only problem is that this gives incorrect answers.

(i_a=44/21, i_b=47/21, and i_c=34/21)

Note - i_1=i_a,i_3=i_b,i_5=i_c

Thanks in advance!